An empirical analysis of demand for water rights transfers and leases in western water markets: a simultaneous approach - Kristiana Hansen; Vardges Hovhannisyan; Catherine Grant (Agricultural and Resource Economics Review)
Water demand continues to increase in the western U.S., straining existing (and forecasted future) supplies. Water transfers – through either the sale of water rights or contractual leases of bounded duration – are now a well-established means of reallocating water to the highest economic benefit. Water is not a typical commodity, however. Significant variability in price across different geographic locations reflects differences in hydrologic conditions, demand and supply, and infrastructure development. These differences will persist even in well-functioning markets due to high transportation costs and user interconnectivity.